2020
DOI: 10.1038/s41598-020-62921-z
|View full text |Cite
|
Sign up to set email alerts
|

tDCS over the inferior frontal gyri and visual cortices did not improve response inhibition

Abstract: The ability to cancel an already initiated response is central to flexible behavior. While several different behavioral and neural markers have been suggested to quantify the latency of the stopping process, it remains unclear if they quantify the stopping process itself, or other supporting mechanisms such as visual and/or attentional processing. the present study sought to investigate the contributions of inhibitory and sensory processes to stopping latency markers by combining transcranial direct current st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 63 publications
(87 reference statements)
4
31
0
Order By: Relevance
“…Inhibitory control processes play an important role in the resolution of response conflicts (Stürmer et al 2000 ; Cisek and Kalaska 2005 ; Taylor et al 2007 ; Verleger et al 2009 ; Tandonnet et al 2011 ; Ocklenburg et al 2011 ; Klein et al 2014 ). It may, therefore, be speculated that the observed specificity of atDCS effects is due to the involvement of inhibitory control processes (but see (Thunberg et al 2020 ) reporting no effects of frontal tDCS on inhibitory control).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory control processes play an important role in the resolution of response conflicts (Stürmer et al 2000 ; Cisek and Kalaska 2005 ; Taylor et al 2007 ; Verleger et al 2009 ; Tandonnet et al 2011 ; Ocklenburg et al 2011 ; Klein et al 2014 ). It may, therefore, be speculated that the observed specificity of atDCS effects is due to the involvement of inhibitory control processes (but see (Thunberg et al 2020 ) reporting no effects of frontal tDCS on inhibitory control).…”
Section: Discussionmentioning
confidence: 99%
“…McGarry and Franks (1997) designed a stop signal task with untypically short SSDs, and found that, based on the shape of the prEMG rising slope, trials could be divided into trials with early and late stopping mechanisms (see Box 1 about interrupted response for details). Further, electroencephalography studies have found that prEMG trials show decreased lateralized readiness potentials and increased frontal negativities (De Jong et al, 1990;van Boxtel et al, 2001). Increased frontal negativities have also been related to awareness of the prEMG in response conflict tasks (Ficarella et al, 2019).…”
Section: Conclusion 3: Premg Provides Unique Information About Stoppingmentioning
confidence: 99%
“…Several further studies attempted to interpret the prEMG within the context of the horse race model. For instance, trials with prEMG seem to roughly correspond to the middle part of the go-RT distribution, indicating that these trials have a relatively fast go process that nonetheless is slow enough to be suppressed by the stop process (De Jong et al, 1990;van Boxtel et al, 2001). Furthermore, the occurrence of the prEMG is dependent on the SSD, as prEMG frequency declines and its amplitude increases with increasing SSD (Coxon et al, 2006).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…2016 ) (but see Schall and Godlove 2012 ; Erika-Florence et al. 2014 ; Thunberg et al. 2020 for counterperspectives on cortical areas involved in stopping control).…”
Section: Introductionmentioning
confidence: 99%